A comparative analysis of the bronchodilatador response measured by impulse oscillometry and spirometry in asthmatic children living at high altitude. (2nd November 2021) - Ramirez, Oscar; Alvarez, Ivan; Aristizabal-Duque, Ricardo; Villamil, Milena; Sossa-Briceño, Monica P.; Rodriguez-Martinez, Carlos E.
Abstract: Objective: Although the assessment of a bronchodilator response (BDR) is a routine and important procedure when performing lung function tests, comparisons between spirometric and oscillometric BDRs in asthmatic children living at high altitude have not been previously reported. The aim of the present study was to compare spirometric and oscillometric BDRs in children living at high altitude, and to identify independent predictors of spirometric and oscillometric BDRs. Methods: Between January and December, 2015, asthmatic children aged between 5 and 17 years old performed impulse oscillometry (IOS) and spirometry during the same visit before and after albuterol administration. The data were analyzed, and children were classified into those positive for oscillometric BDR only, those positive for spirometric BDR only, those positive for both BDRs, and those negative for both BDRs. Results: Ninety-three asthmatic children (56 boys, 37 girls), with a median (IQR) age of 11 (8-13) years, made up the study population. Among the total of 93 participants, 13 (14.0%), 4 (4.3%), 0 (0%), and 76 (81.7%) were positive for spirometric BDR only, positive for oscillometric BDR only, positive for both BDRs, and negative for both BDRs, respectively. Age and baseline lung function were identified as significant predictors of positive spirometric BDR. Conclusions: The present study shows poor concordance between positive spirometric and oscillometric BDRs, with a greater proportion of patients with a spirometric BDR when compared to those with positive oscillometric BDR. Additionally, age and baseline lung function are useful for predicting spirometric BDR results.